Analisis Perbandingan Usaha Tani Benih Padi Bersertifikat dan Non Bersertifikat di Desa Pematang Johar (Studi Kasus Kabupaten Labuhan Deli Kecamatan Deli Serdang) - Putri Helena Panjaitan; Gustami Harahap; Mitra Musika Lubis (Jurnal Agriuma, 2020)
This study aims to: (1) find out how much the comparison of certified and non-certified seed farming income, (2) find out what factors influence the income of certified and non-certified seed farming. The sampling method uses the Proportionate Sratified Random Sampling method. The data used are primary and secondary data. The analytical method used is four classic assumption tests (simultaneous test, partial test, determinant test and multicollinearity test) and one-way ANOVA test. The results of this study indicate that there is no significant comparison between the income of certified rice seed farming that is the mean value of 10,424,585.71 with non-certified rice seed farming income that is the mean value of 10,841,386.67. Factors affecting the income of certified rice seed farming arexc land area, production, fertilizer costs, pesticide costs, labor costs, and rice prices. Whereas that has no effect is the cost of seeds. Factors that influence the income of non-certified rice seed farming are production, fertilizer costs, pesticide costs, labor costs, and prices. Meanwhile, those who have no effect are land area and seed cost.